A theory of system justification - Jost, John T. (Harvard University Press, 2020)
"Psychologist John T. Jost has spent decades researching poor people who vote for policies of inequality and women who think men deserve higher salaries. He argues that the persecuted often justify and defend the very social systems that oppress them because doing so serves a fundamental need for certainty, security, and social acceptance"--